2004
DOI: 10.1029/2003gl019225
|View full text |Cite
|
Sign up to set email alerts
|

The dependence of traction evolution on the earthquake source time function adopted in kinematic rupture models

Abstract: [1] We compute the temporal evolution of traction by solving the elasto-dynamic equation and by using the slip velocity history as a boundary condition on the fault plane. We use different source time functions to derive a suite of kinematic source models to image the spatial distribution of dynamic and breakdown stress drop, strength excess and critical slip weakening distance (D c ). Our results show that the source time functions, adopted in kinematic source models, affect the inferred dynamic parameters. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 16 publications
2
39
0
Order By: Relevance
“…And it is pointed out that a tiny change in slip velocity function results in very different slip weakening behaviors (Piatanesi et al 2004;Tinti et al 2009). Mikumo et al (2003) and Fukuyama et al (2003) proposed a technique for the estimation of slip weakening distance from the slip time function on the fault.…”
Section: Slip-weakening Distancementioning
confidence: 99%
“…And it is pointed out that a tiny change in slip velocity function results in very different slip weakening behaviors (Piatanesi et al 2004;Tinti et al 2009). Mikumo et al (2003) and Fukuyama et al (2003) proposed a technique for the estimation of slip weakening distance from the slip time function on the fault.…”
Section: Slip-weakening Distancementioning
confidence: 99%
“…As discussed above, the inadequate resolution and the limited frequency bandwidth, which characterize inverted kinematic models, reduce the ability to infer the real dynamic traction evolution everywhere on the fault plane. Many recent papers have investigated the limitations of using poorly resolved kinematic source models (Guatteri and Spudich, 2000;Piatanesi et al, 2004;Spudich and Guatteri 2004). We discuss these issues in further detail below.…”
Section: Inferring Traction Evolutionmentioning
confidence: 99%
“…Moreover, source time functions compatible with earthquake dynamics and suitable for waveform inversions are becoming commonly available (see Piatanesi et al, 2004;Tinti et al, 2005b;Dreger et al, 2007;Cirella et al, 2006). Finally, Tinti et al (2005a and have discussed in detail the fidelity of calculations of breakdown work and D c and concluded that, in agreement with Guatteri and Spudich (2000), the estimates of W b are quite stable despite the limited available resolution in kinematic source models, while the D c parameter is more difficult to constrain.…”
Section: Inferring Traction Evolutionmentioning
confidence: 99%
See 2 more Smart Citations